Vai trò điều tiết của nội dung do người dùng tạo ra trong mối quan hệ giữa các kích thích xã hội và hành vi bầy đàn trong mua sắm trực tuyến - Nguyễn Minh , Nhật; Lê Uyên , Nhi; Nguyễn Lê Ngọc , Vy; Phạm , Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The development of digital transformation alongside social media has contributed to a rise in herd buying behaviour, particularly among young consumers born after 1995. Rooted in the Stimulus-Organism-Response (S-O-R) framework, this study evaluates the roles of electronic word-of-mouth, spokesman credibility, and user-generated content as environmental stimuli influencing consumer herd behavior, which in turn leads to a response in online purchase intention. The study employed a convenience sampling method to survey 310 social media users and applied structural equation modeling to validate the proposed hypotheses. Empirical findings suggest that electronic word-of-mouth and spokesman credibility have a significant impact on consumer herd behavior. Furthermore, user-generated content not only exerts a direct impact but also plays a moderating role in the relationships among the related variables. Based on these findings, the study reinforces the applicability of the S-O-R framework in the context of e-commerce. It proposes several practical implications to assist businesses in optimizing their strategies for approaching this younger generation of consumers